2012
DOI: 10.2164/jandrol.111.013458
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low‐Level Laser Light Exposure on Sperm Motion Characteristics and DNA Damage

Abstract: The objective of this study was to determine the effects of low-level laser light exposure on the motility of spermatozoa and on DNA damage. Thirty-three semen samples were collected for routine analysis and were classified as normospermic, oligospermic, or asthenospermic. After routine semen analysis was performed, residual semen was divided into treated and control aliquots. Treated samples were exposed to a 30-second infrared laser pulse of 50 mW/cm 2 at 905 nm, a wavelength thought to increase light-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
28
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 21 publications
5
28
0
9
Order By: Relevance
“…These methods are not always successful and could benefit from additional means of improving fertilization. Several studies have indicated that low doses of red light cause an increase in sperm motility and overall fertilizing potential in several species1234. By increasing sperm swimming speed in vitro , the likelihood of contact with the oocyte is increased.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These methods are not always successful and could benefit from additional means of improving fertilization. Several studies have indicated that low doses of red light cause an increase in sperm motility and overall fertilizing potential in several species1234. By increasing sperm swimming speed in vitro , the likelihood of contact with the oocyte is increased.…”
mentioning
confidence: 99%
“…However, DNA damage was not tested in this the study. Several studies235 have also used the well-known computer-assisted sperm analysis (CASA) system for measurement of sperm motility by measuring swimming speed directly after light irradiation. Such studies assume that optically induced effects last several minutes following irradiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Более того, есть вполне убедительные дока-зательства, что низкоинтенсивный, как лазерный, так и некогерентный, свет позволяет существенно повысить выживаемость, подвижность и скорость перемещения сперматозоидов человека [52][53][54][55].…”
Section: +unclassified
“…Лишь в одной работе использовали импульсный ИК-лазер (длина волны -905 нм) мощностью 50 Вт (длительность импульса -200 нс), плотность мощ-ности -50 Вт/см 2 , причем даже при далеко неопти-мальной (мягко говоря) частоте 10 000 Гц наблюдали повышение подвижности и отсутствие повреж-дений ДНК. Вероятно, положительный результат был получен вследствие небольшой экспозиции (30 с), причем он отсутствовал при нормо-и асте-носпермии, а наблюдался, и весьма значительный (в 8,4 раза), только при олигоастенотератозооспер-мии через 30 мин после лазерного освечивания [55]. Это подтверждает известное мнение, что степень влияния НИЛИ коррелирует с выраженностью имеющихся нарушений [31].…”
Section: +unclassified